Peran Guru dalam Meningkatkan Mutu Pembelajaran - Yadi Sutikno; Hosan Hosan; Irawati Irawati (STAB Maitreyawira, 2022)
Based on observations, there are not many studies that explain the role of teachers in improving the quality of learning. Whereas research on the role of teachers in improving the quality of learning is important. Based on these observations, research will be conducted on the role of teachers in improving the quality of learning. This research method usesqualitative research methods with the type of literature study. The teacher's role in improving the quality of learning is to implement a learning system according to conditions, the knowledge provided is in accordance with the development of science and technology, quality learning resources for students, the language in learning resources can be understood, and to provide character education to students.